2020
DOI: 10.5056/jnm19072
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Symptoms in Patients With Functional Dyspepsia and Irritable Bowel Syndrome: Relations to Ultrasound Measurements and Psychological Factors

Abstract: Background/Aims Dyspeptic symptoms are common in patients with functional gastrointestinal (GI) disorders, and may be related to visceral hypersensitivity. We aim to explore the relation between visceral hypersensitivity by using an ultrasonographic meal test and questionnaires in patients with irritable bowel syndrome (IBS) and/or functional dyspepsia (FD). Methods Patients (FD, n = 94; IBS, n = 88; IBS + FD, n = 66, healthy controls [HC], n = 30) were recruited consecutively and examined with ultrasound of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
3
19
0
1
Order By: Relevance
“…These measurements, as well as symptom scoring, were repeated at 10 and 20 min postprandially. Normal values for the UMAT are published in Steinsvik et al 16 In this paper, we used fasting antral area >5.4 cm 2 as a cutoff value for enlarged fasting antral area, based on mean plus two standard deviations from the healthy controls study.…”
Section: Methodsmentioning
confidence: 99%
“…These measurements, as well as symptom scoring, were repeated at 10 and 20 min postprandially. Normal values for the UMAT are published in Steinsvik et al 16 In this paper, we used fasting antral area >5.4 cm 2 as a cutoff value for enlarged fasting antral area, based on mean plus two standard deviations from the healthy controls study.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the construction of the database, we continued to use the Rome III to have homogeneous groups of patients. Finally, the present study lacks consideration of many lifestyle factors associated with OFGIDs as the response to food, 46 smocking, 47 and psychological status 48 ; these factors affect as well the severity of the diseases as the quality of life of these patients.…”
Section: Discussionmentioning
confidence: 98%
“…No difference in the rate of anxiety and depression was obtained between patients with organic and functional diseases of the digestive system. Many previous studies have focused on the psychosomatic status of patients with functional gastrointestinal disorders (FGIDs) such as irritable bowel syndrome (IBS) and functional dyspepsia (FD) [33][34][35][36]. It has been reported that in general hospitals, more than half of the patients with depression or anxiety visited the nonpsychiatric department for the first time.…”
Section: Discussionmentioning
confidence: 99%